FOSTER FAMILY AS A FORM OF FOSTER EDUCATION - Падун, Роман Володимирович (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2020)
Purpose: to investigate the legal basis, features and essence of foster care of orphans and children deprived of parental care. Research methods: induction, used to analyze judicial practice on the placement of orphans and children deprived of parental care. Results: the general provisions on the procedure for transferring children to foster care with the subsequent definition of a specific form of such education are analyzed. Discussion: the peculiarities of the legal regulation of the foster family as forms of foster care are singled out. According to the legislation of Ukraine, parents are obliged to maintain their children until they reach the age of majority, to take care of the child’s health, physical, spiritual and moral development. In addition to the significant amount of parental authority to raise a child, family law stipulates that parents’ refusal of a child is unjustified and contrary to the moral principles of society. In addition, parents’ evasion of parental responsibilities is grounds for bringing them to justice. However, some parents, ignoring the requirements of the law and ignoring moral principles, do not fulfill their parental responsibilities, as a result of which the number of children deprived of parental care is constantly growing in our country. The author concludes that, unfortunately, such a category of the population as orphans and children deprived of parental care has been and will be. First of all, this is due to the objective factors of today: the low level of material security of families, the low level of their legal awareness and compliance, and hence the lack of adequate social protection. The situation is aggravated by certain subjective factors: the death of parents, or their inability (unwillingness) to raise children. Foster care, as one of the forms of foster care, undoubtedly plays an important role in solving the problem of providing children deprived of parental care with family upbringing. However, it must be acknowledged that the main task of the state should be to preserve the family as one of the main institutions of positive socialization of children, because all children should grow up in a family environment, in an atmosphere of happiness, love and understanding.